CHARACTERIZATION OF BIODEGRADABLE FOAM FROM OIL PALM EMPTY FRUIT BUNCH CELLULOSE, CASSAVA STARCH, AND POLYVINYL ALCOHOL - Idha Silviyati; Aisyah Suci Ningsih; Desti Lidya; Endang Supraptiah; Sri Murda Niati; Bimo Satrio (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2026)
Styrofoam is widely used for food packaging, but its poor degradability and harmful compounds pose serious environmental and health concerns. This study developed biodegradable foam from oil palm empty fruit bunch (OPEFB) cellulose and cassava starch through thermopressing, with polyvinyl alcohol (PVA) added to improve product performance. The formulations varied in cassava starch-to- OPEFB cellulose ratios (1:1, 2:1, 3:1, and 4:1) and PVA concentrations (0%, 5%, and 10%). Results showed that increasing the starch ratio and PVA concentration significantly affected water absorption, tensile strength, thickness, and biodegradation rate. The optimum formulation was obtained at a 4:1 starch-to-cellulose ratio with 10% PVA, yielding water absorption of 10.04%, tensile strength of 2.362 MPa, thickness of 0.114 mm, and complete biodegradation within 48.16 days. All biofoam characteristics complied with SNI 7188.7:2016 and JIS Z1707:2017 standards.